ANALISIS HUBUNGAN PENDIDIKAN IBU TERHADAP KONSUMSI MAKANAN ANAK YANG MENGANDUNG BORAKS DENGAN MENGGUNAKAN BAHAN DASAR KUNYIT - Nisah, Khairun (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2015)
The study is conducted to analyse foods which are marketed in Aceh since March 2015. Within 3 months of observation, the study took in total 98 samples, 18 of which are positive for borax content. Food types commonly containing this dangerous substance are yellow noodle, fried tofu ball with peanut sauce, and fried meatball, with borax determination using indicator turmeric. The assumption is a significant correlation between mother’s educations to high level consumption of borax containing foods for children in Aceh, since the average mother’s educations in Aceh are low. Therefore, several factors in mother’s educations need to be revealed. The study area is focused on the area of Aceh Besar Regency, where cases for the borax containing foods were highly found. The data used in this study are data findings for the use of borax in Aceh Besar Regency, the observation of mother’s education through social media, deep interview to several housewife mothers, several public figures and several communities with knowledge in local customs, in addition of observation on object related to the use of boraxs. The interview result is inserted to a matrix table in order to obtain information related to mother’s education. The analysis is done in descriptive-qualitative method. One of the study results shows a correlation between mother’s educations to children food’s consumption. The better mother’s education will lead to healthier children food’s consumption. Environmental factors also play a role.